added a little text

This commit is contained in:
Jeremy Siek 2019-05-20 10:15:45 -04:00
parent b91933d7db
commit b2053ddc1a

View file

@ -704,11 +704,14 @@ The proof is by induction on the term `M`.
The last lemma needed to prove `sub-sub` states that the `exts`
function distributes with sequencing. It is a corollary of
`commute-subst-rename`. We describe the proof below.
`commute-subst-rename` as described below. (It would have been nicer
to prove this directly by equational reasoning in the σ algebra, but
that would require the `sub-assoc` equation, whose proof depends on
`sub-sub`, which in turn depends on this lemma.)
\begin{code}
exts-seq : ∀{Γ Δ Δ′} {σ₁ : Subst Γ Δ} {σ₂ : Subst Δ Δ′}
→ ∀ {A} → (exts σ₁ ⨟ exts σ₂) {A} ≡ exts (σ₁ ⨟ σ₂)
→ ∀ {A} → (exts σ₁ ⨟ exts σ₂) {A} ≡ exts (σ₁ ⨟ σ₂)
exts-seq = extensionality λ x → lemma {x = x}
where
lemma : ∀{Γ Δ Δ′}{A}{x : Γ , ★ ∋ A} {σ₁ : Subst Γ Δ}{σ₂ : Subst Δ Δ′}